A Systematic Review of Ethanol and Fomepizole Use in Toxic Alcohol Ingestions. (31st January 2013) - Beatty, Lorri; Green, Robert; Magee, Kirk; Zed, Peter
Abstract : Objectives . The optimal antidote for the treatment of ethylene glycol or methanol intoxication is not known. The objective of this systematic review is to describe all available data on the use of ethanol and fomepizole for methanol and ethylene glycol intoxication. Data Source . A systematic search of MEDLINE and EMBASE was conducted. Study Selection . Published studies involving the use of ethanol or fomepizole, or both, in adults who presented within 72 hours of toxic alcohol ingestion were included. Our search yielded a total of 145 studies for our analysis. There were no randomized controlled trials, and no head-to-head trials. Data Extraction . Variables were evaluated for all publications by one independent author using a standardized data collection form. Data Synthesis . 897 patients with toxic alcohol ingestion were identified. 720 (80.3%) were treated with ethanol (505 Me, 215 EG), 146 (16.3%) with fomepizole (81 Me, 65 EG), and 33 (3.7%) with both antidotes (18 Me, 15 EG). Mortality in patients treated with ethanol was 21.8% for Me and 18.1% for EG. In those administered fomepizole, mortality was 17.1% for Me and 4.1% for EG. Adverse events were uncommon. Conclusion . The data supporting the use of one antidote is inconclusive. Further investigation is warranted.